2007
DOI: 10.1055/s-2007-966591
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized controlled trial of transjugular intrahepatic portosystemic shunt versus cyanoacrylate injection in the prevention of gastric variceal rebleeding

Abstract: TIPS proved more effective than glue injection in preventing rebleeding from gastric varices, with similar survival and frequency of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
224
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(232 citation statements)
references
References 20 publications
2
224
0
6
Order By: Relevance
“…18 Costeffective analyses comparing NBC injection with TIPS have suggested that NBC is a safe and effective treatment for gastric variceal bleeding that can be provided at a significantly lower cost compared with TIPS placement. 19,20 The usefulness of TIPS is also limited by its availability only in major centers. 17 Balloon occluded retrograde transvenous obliteration has been used successfully for GV obliteration, primarily in Japan, as an elective procedure, but is unsuitable for acute gastric variceal bleeding and requires the presence of a spontaneous gastro-renal shunt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Costeffective analyses comparing NBC injection with TIPS have suggested that NBC is a safe and effective treatment for gastric variceal bleeding that can be provided at a significantly lower cost compared with TIPS placement. 19,20 The usefulness of TIPS is also limited by its availability only in major centers. 17 Balloon occluded retrograde transvenous obliteration has been used successfully for GV obliteration, primarily in Japan, as an elective procedure, but is unsuitable for acute gastric variceal bleeding and requires the presence of a spontaneous gastro-renal shunt.…”
Section: Discussionmentioning
confidence: 99%
“…21 The preferred first line treatment for acute gastric variceal bleeding is endoscopic obliteration with NBC. 20,22 Endoscopic injection of tissue glue for gastric variceal bleeding was first reported in 1986 by Soehendra et al 12 Since then, this method has been adopted widely and proved to be effective in the hemostasis of gastric variceal bleeding. [23][24][25][26][27][28]30 NBC, a liquid monomer, undergoes rapid exothermic polymerization on contact with living tissues, and this property of the compound has been used to eradicate and treat GV.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding was controlled in most patients, comparable to the success rate for bleeding esophageal varices 45 . In another small series with 32 patients with refractory bleeding gastric varices, TIPS placement achieved homeostasis in 90% in those with active bleeding, and re-bleeding rates were 14%, 26%, and 31%, respectively at 1 month, 6 months, and 1 year 48 . In addition, TIPS has also been compared to glue therapy for bleeding gastric varices 4849 .…”
Section: Refractory Bleeding From Gastric Varices and Portal Hypertenmentioning
confidence: 93%
“…It is recommended that TIPS be used in acute bleeding from fundal varices when EVO is unavailable or if rebleeding occurs after EVO; however, this has not been evaluated prospectively. A small single-center study comparing EVO versus TIPS in the prevention of recurrent hemorrhage in patients in whom acute gastric variceal hemorrhage was controlled with EVO showed similar rebleeding rates, but again fewer than 50% of the patients were bleeding from fundal varices [46]. …”
Section: Diagnosis and Treatment Of Acute Gastric Variceal Bleedingmentioning
confidence: 98%